Antibacterial and Antifungal Activities of Ethiopian Medicinal Plants: A Systematic Review - Dereje Nigussie; Dereje Nigussie; Gail Davey; Gail Davey; Takele Beyene Tufa; Malcolm Brewster; Belete Adefris Legesse; Abebaw Fekadu; Abebaw Fekadu; Eyasu Makonnen; Eyasu Makonnen (Frontiers Media S.A., 2021)
Background: Podoconiosis and lymphatic filariasis are the most common causes of lower limb lymphoedema in the tropics. Many sufferers experience frequent painful episodes of acute bacterial infection. Plant based traditional medicines are used to treat infections in many countries and are culturally established in Ethiopia. Ethiopian medicinal plants found to have antibacterial and antifungal activities were reviewed with the aim of increasing information about the treatment of wound infections in patients with lymphoedema.Methods: This study collates data from published articles on medicinal plants with antibacterial and antifungal activities in Ethiopia. A systematic search of Scopus, EMBASE, PUBMED/MEDLINE and Google Scholar was undertaken. The Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines were followed. The protocol was registered on PROSPERO with registration number CRD42019127471. All controlled studies of in vitro antibacterial and antifungal activities were considered. All articles containing the descriptors published until June 28, 2019 were included. The outcome was measured as percent inhibition of microbial growth. For quality assessment of individual in vitro studies, OECD guidelines and the WHO-Good Laboratory Practice (GLP) handbook were used.Results: Seventy-nine studies met the inclusion criteria. A total of 150 plant species and three compounds had been tested against 42 species of bacteria, while 43 plant species had been tested against 22 species of fungus.Conclusion: Materials derived from several Ethiopian medicinal plants have been shown to have promising activity against a variety of bacteria and fungi. Those derived from Azadiractha indica A. Juss. and Lawsonia inerms L. are the most extensively studied against a wide range of gram-negative and positive bacteria, and fungal species.